2017
DOI: 10.1111/jocn.13831
|View full text |Cite
|
Sign up to set email alerts
|

Registered nurses’ perception of self‐efficacy and competence in smoking cessation after participating in a web‐based learning activity

Abstract: Findings from this study will be of particular interest to educators in healthcare settings who can devise further development of web-based learning activities.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
16
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(20 citation statements)
references
References 33 publications
0
16
0
Order By: Relevance
“…After web‐based cessation training, previous studies showed an increase in healthcare provider self‐efficacy, competency, skill, and smoking cessation guideline adherence when it came to providing cessation services to the patients (Bialous et al, 2017; De Ruijter, Candel, Smit, De Vries, & Hoving, 2018; Rosvall & Carlson, 2017; Sarna et al, 2016). The current study demonstrated that implementing an evidenced‐based, e‐learning education program has a positive impact on the healthcare provider’s knowledge and confidence in helping oncology patients quit smoking.…”
Section: Discussionmentioning
confidence: 99%
“…After web‐based cessation training, previous studies showed an increase in healthcare provider self‐efficacy, competency, skill, and smoking cessation guideline adherence when it came to providing cessation services to the patients (Bialous et al, 2017; De Ruijter, Candel, Smit, De Vries, & Hoving, 2018; Rosvall & Carlson, 2017; Sarna et al, 2016). The current study demonstrated that implementing an evidenced‐based, e‐learning education program has a positive impact on the healthcare provider’s knowledge and confidence in helping oncology patients quit smoking.…”
Section: Discussionmentioning
confidence: 99%
“…The analysis also suggested that pharmacy staff (including those without NCSCT training) were using consultation skills and appropriate words and phrases which were taught in their STOP intervention training. From a social cognitive theoretical perspective,36 this potentially demonstrates improved knowledge through vicarious learning and increased self-efficacy to provide basic SSS information to clients.…”
Section: Discussionmentioning
confidence: 99%
“…The 15 articles reviewed and analyzed included nine quantitative cross-sectional studies (Chatdokmaiprai et al, 2017; Choi & Kim, 2016; Connolly et al, 2013; Fore et al, 2013; Ganz et al, 2015; Leitlein et al, 2013; Smit et al, 2013; Taniguchi et al, 2016), one quantitative prospective design (Sarna et al, 2014), three mixed-method qualitative–quantitative research designs (Guo et al, 2015; Katz et al, 2016; Rosvall & Carlson, 2017), and two qualitative interview designs (Ostlund et al, 2015; Schwindt et al, 2016).…”
Section: Characteristics Of the Studiesmentioning
confidence: 99%
“…Two of the research designs used pre-and post-surveys to evaluate educational programs and outcomes of training (Fore et al, 2013; Sarna et al, 2014). Mixed-method studies interviewed volunteers from larger surveys for closer examination (Guo et al, 2015; Katz et al, 2016; Rosvall & Carlson, 2017). Two studies used semi-structured interviews for content analysis (Ostlund et al, 2015) and audiotaped interviews for theme analysis (Schwindt et al, 2016).…”
Section: Characteristics Of the Studiesmentioning
confidence: 99%
See 1 more Smart Citation